Nickel electrodeposition from novel citrate bath - 李超群 李新海 王志兴 郭华军 (Transactions of Nonferrous Metals Society of China, 2007)
A new type of electroplating bath suitable for nickel electrodeposition was developed. Trisodium citrate was used as a complexing agent and a buffer in the bath. The buffering capacity between trisodium citrate and boric acid were compared. The effects were investigated under different conditions of bath composition, current density, pH and temperature on the potentiodynamic cathodic polarization curves, cathodic current efficiency and throwing index, as well as the electrical conductivity of these baths. The optimum conditions for producing sound and satisfactory nickel deposits were： NiSOn6H2O350 g/L, NiCl2·6H2O 45 g/L and Na3C6H5 O7 30 g/L at pH=4 and 55 ℃. The surface morphology of the as-plated Ni deposit was examined by SEM. The results reveal that the nickel deposition obtained from the optimum conditions are composed of compact, non-porous fine grains covering the entire surface. X-ray analysis shows that nickel deposits obtained from the citrate bath have a fine crystal structure compared with deposits from the Watts bath.